Bank-By-Bank Credit Ceilings : Issues and Experiences - Farahbaksh, Mitra (IMF Working Papers; Working Paper ;, 1996)
Many central banks have abandoned credit ceilings in favor of monetary control frameworks based on indirect instruments. In the long run, ceilings limited competition, hampered the development of a money market, and caused disintermediation. Despite the many distortions associated with the use of credit ceilings, some countries continue to employ them, particularly during the transitional period before full reliance on indirect monetary instruments. The paper argues that the careful attention to design can help reduce distortions typically associated with the use of credit ceilings. It identifies a series of principles that may be followed in designing a system that can minimize those distortions.